2017
DOI: 10.1007/s00442-017-3866-8
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in growth patterns among strains of the lethal fungal pathogen Batrachochytrium dendrobatidis across extended thermal optima

Abstract: The thermal sensitivities of organisms regulate a wide range of ecological interactions, including host–parasite dynamics. The effect of temperature on disease ecology can be remarkably complex in disease systems where the hosts are ectothermic and where thermal conditions constrain pathogen reproductive rates. Amphibian chytridiomycosis, caused by the pathogen Batrachochytrium dendrobatidis (Bd), is a lethal fungal disease that is influenced by temperature. However, recent temperature studies have produced co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 53 publications
5
74
0
2
Order By: Relevance
“…These findings are consistent with other field studies (Berger et al 2004, Kriger and Hero 2006, 2007, Bosch et al 2007, Murphy et al 2011, Rowley and Alford 2013, Petersen et al 2016, with species distribution models (SDMs) for Bd (Puschendorf et al 2009, Murray et al 2011 and with studies of the thermotolerance of Bd in vitro (Piotrowski et al 2004, Woodhams et al 2008, Voyles et al 2017, which have all found evidence to support a decrease in pathogen survival and/or host infection at high temperatures. In our field study, Bd prevalence dropped steeply following periods when the daily maximum air temperature exceeded~27°C.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with other field studies (Berger et al 2004, Kriger and Hero 2006, 2007, Bosch et al 2007, Murphy et al 2011, Rowley and Alford 2013, Petersen et al 2016, with species distribution models (SDMs) for Bd (Puschendorf et al 2009, Murray et al 2011 and with studies of the thermotolerance of Bd in vitro (Piotrowski et al 2004, Woodhams et al 2008, Voyles et al 2017, which have all found evidence to support a decrease in pathogen survival and/or host infection at high temperatures. In our field study, Bd prevalence dropped steeply following periods when the daily maximum air temperature exceeded~27°C.…”
Section: Discussionsupporting
confidence: 91%
“…Third, we predicted that tropical amphibian hosts should experience greater susceptibility to Bd following variable temperatures because the thermal breadths of these hosts should be narrower than those of temperate hosts as they typically experience less variation in temperature . Meanwhile, the thermal breadths of Bd strains are typically much broader than those of hosts and do not vary much across latitude (Cohen et al 2017;Voyles et al 2017). Fourth, we predicted that hosts from high elevations would experience greater sensitivity to Bd under thermal mismatches than hosts from low elevations because they generally experience lower interannual and seasonal thermal variation (Brattstrom 1968;Navas 1996; also supported by our datasee Results).…”
Section: Introductionsupporting
confidence: 68%
“…; Voyles et al . ). Fourth, we predicted that hosts from high elevations would experience greater sensitivity to Bd under thermal mismatches than hosts from low elevations because they generally experience lower interannual and seasonal thermal variation (Brattstrom ; Navas ; also supported by our data – see Results).…”
Section: Introductionmentioning
confidence: 97%
“…Four of the five traits we measured have been linked to virulence in vivo. Larger Bd zoospore size, larger zoosporangium size, slower growth rate and higher carrying capacity are correlated with higher Bd infection loads and higher amphibian mortality (Becker et al., ; Fisher et al., ; Lambertini et al., ; Piovia‐Scott et al., ; Voyles, ; Voyles et al., ). Bd‐Brazil produced the smallest zoospores and zoosporangia across temperatures, which may explain the lower virulence and infectiveness of Bd‐Brazil compared to Bd‐GPL and the GPL‐Brazil hybrid (Greenspan et al., ; Jenkinson et al., ; Rodriguez, Becker, Pupin, Haddad, & Zamudio, ).…”
Section: Discussionmentioning
confidence: 99%
“…We grew isolates from nine Bd genotypes (Table ) at three temperatures in 96‐well plates using a full‐factorial design. We selected three temperatures (12, 18 and 24°C) within the temperature range for Bd growth (Piotrowski et al., ; Stevenson et al., ; Voyles et al., ). We selected isolates that were genotyped in previous studies (Jenkinson et al., ; Schloegel et al., ) and represented genetic diversity within and among Bd lineages, including the Bd‐Brazil lineage, a Bd‐Brazil‐GPL hybrid and several Bd‐GPL genotypes.…”
Section: Methodsmentioning
confidence: 99%